Progressive encephalomyelitis with rigidity and myoclonus: a syndrome with diverse clinical features and antibody responses. - Shugaiv, E; Leite, M; Şehitoğlu, E; Woodhall, M; Çavuş, F; Waters, P; İçöz, S; Birişik, Ö; Uğurel, E; Ulusoy, C; Kürtüncü, M; Vural, B; et al. (2013)
BACKGROUND/AIMS: To better characterize progressive encephalomyelitis with rigidity and myoclonus (PERM) syndrome and identify novel PERM phenotypes. METHODS: The clinical features and antibody status of PERM patients were investigated using immunoblots, cell-based assays, RIA, protein macroarray and ELISA. RESULTS: Two patients with supratentorial involvement showed abnormal PET or EEG findings. One patient was discovered to have renal cell carcinoma, and protein macroarray revealed Ma3-antibodies. Another patient with leucine-rich, glioma-inactivated 1 (LGI1) and glutamic acid decarboxylase (GAD) antibodies showed a good response to immunotherapy. CONCLUSION: The heterogeneity of the immunological features suggests that PERM is caused by diverse pathogenic mechanisms. Seropositivity to well-characterized neuronal cell surface antigens might indicate a good treatment response.